Drought stress on early growth of Diospyros mespiliformis Hochst ex A. Rich in Jega, Northern Nigeria (2012)
Trees face rising drought stress and mortality with global warming and it is vital that adequate information is available on the tolerance levels of tree species. In 2012, seedlings of Diospyros mespiliformis Hochst ex A. Rich were evaluated for response to varied levels of water availability at the Aliero Teaching and Research Farm, Kebbi State University of Science and Technology, Jega, Kebbi State, Nigeria. Twelve uniformly growing potted seedlings were selected and exposed to four watering frequencies (daily, once in three days, weekly and fortnightly) in a screen house. For each watering event, 200 ml of water was administered to the soil of each potted seedling. Seedling height and collar diameter were measured, while number of leaves were counted fortnightly for 16 weeks. The data were analysed using descriptive statistics and analysis of variance, at p<0.05 level of significance. A hundred percent survival rate was observed in all treatments. Seedlings that were watered daily had the highest height (13.53 ± 2.66 cm) and collar diameter (3.41 ± 0.44 mm). The treatments resulted in 283%, 133%, 98% and 125% increase in height, as well as 100%, 89%, 57% and 40% increase in collar diameter of seedlings watered daily, once in 3 days, weekly and fortnightly, respectively. Time of experiment had a significant influence on the height and collar diameter growth of seedlings in the four treatments while watering frequency only had a significant effect on collar diameter of the seedlings, after 16 weeks. However, posthoc analysis showed that only the collar diameter of daily watered seedlings differed from other treatments. Although, delayed watering reduced the rate of growth, it did not hinder it. The least watered seedlings had the lowest number of leaves (6) after 16 weeks. The study showed that fortnight supply of water was sufficient for the early growth and development of D. mespiliformis seedlings. The apparent drought tolerance of the species may be an indication of a good candidate species for plantation establishment under dry and warm conditions which are imminent in the event of climate change